Waste Management Through the TPS3R Program for Urban Communitiesin Optimizing the Implementationof Government Number 81 of 2012 - Destina Anggiyanti; Ubaidillah Kamal (Universitas Negeri Semarang, 2026)
This study aims to analyze how the TPS3R Program can be optimally implemented to meet the waste management standards stipulated in Government Regulation Number 81 of 2012. The main problem studied is the gap between normative provisions regarding waste reduction and handling based on the Reduce, Reuse, Recycle (3R) principle and its implementation conditions in various urban areas. The method used is normative legal research with a statutory regulatory approach linked to empirical conditions through a literature study of primary, secondary, and tertiary legal sources. The analysis is conducted by comparing normative provisions (das sollen) with the reality of implementation in the field (das sein). The results of the study indicate that normatively the legal framework related to TPS3R is adequate and provides a systematic, comprehensive, and sustainable basis for local governments in managing waste. However, in practice, various challenges remain, including limited facilities and infrastructure, dependence on regional budgets and community contributions for funding, uneven institutional capacity, and fluctuating levels of community participation. Differences in success rates between cities indicate that the program's effectiveness is greatly influenced by the synergy between regulations, institutional support, and changes in community behavior. Therefore, it is necessary to strengthen guidance, provide economic incentives, innovate waste processing technology, and improve coordination between stakeholders so that 3R-based waste management can run effectively, measurably, and sustainably.